Formulation and Characterization of Sungkai Leaf Extract Nanoemulsion - Dista, Rama; Larasati, Cindy; Ayuningsih, Sylvia; Anggraeni, Nurah; Batubara, Irmanida (Al-Kimia, 2022)
Sungkai (Peronema canescens Jack) leaves are empirically used for various treatments, and their efficacy can be enhanced using nanoparticle technology, especially nanoemulsions. The purpose was to find the best nanoemulsion formula (NES) containing sungkai leaf extract (EDS). Sungkai leaves were extracted with 70% ethanol, and the compounds were determined by liquid chromatography-mass spectrometry. NES was formed by mixing EDS (260, 400, and 530 mg), VCO, tween80, PEG400, soy lecithin, sodium alginate, and deionized water. The NES formed were characterized by particle size, polydispersity index (PDI), zeta potential, pH, viscosity, percent transmittance, and physical stability test. The results showed that EDS contains at least seven compounds, with eupatilin as a dominant compound. The characterization results obtained NES with a particle size range of 270–520 nm with a PDI value of 0.413–0.608. NES was categorized as stable with a zeta potential value of -45.9 to -48.7 mV and no phase separation based on the centrifugation test. NES has a viscosity of about 1.90–2.03 cP, pH 7, and a percent transmittance of 93–98%. The best formula is the formula with EDS F1 (260 mg). Thus, NES has the potential for the development of multiple treatment targets.